2012
DOI: 10.1016/j.placenta.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin augments the inflammatory IL6 response in the choriodecidua

Abstract: Intrauterine infection frequently leads to preterm birth (PTB), with the pathophysiology involving activation of the innate immune system and its associated inflammatory response. The choriodecidua produces relaxin (RLN) and elevated levels are associated with preterm premature rupture of the fetal membranes. However, it is not increased in bacterially-mediated PTB, but may act as an endogenous sterile inflammatory mediator. Elevated systemic RLN levels from the corpus luteum are also associated with PTB, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Our data and that of others, who have reported that decidual neutrophils in term pregnancies provide a rich source of extracellular matrix proteases 4,16,[178][179][180] and cytokines, 12,33,74,80,92,181 suggest that granulocytes may play a role before and during spontaneous labor at term (before labor for the preparative stages for parturition). As the depletion of neutrophils in the mouse does not affect the timing or course of labor 132 and that other leukocytes and stromal cells produce these and other related immunological media-tors, 83,[182][183][184][185][186][187][188] it would seem that granulocytes are not an absolutely required for labor in mice. We favor a model in which there is cooperation of the different cell types to achieve normal parturition at term.…”
Section: What Is the Role Of Granulocytes In The Choriodecidua Duringmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data and that of others, who have reported that decidual neutrophils in term pregnancies provide a rich source of extracellular matrix proteases 4,16,[178][179][180] and cytokines, 12,33,74,80,92,181 suggest that granulocytes may play a role before and during spontaneous labor at term (before labor for the preparative stages for parturition). As the depletion of neutrophils in the mouse does not affect the timing or course of labor 132 and that other leukocytes and stromal cells produce these and other related immunological media-tors, 83,[182][183][184][185][186][187][188] it would seem that granulocytes are not an absolutely required for labor in mice. We favor a model in which there is cooperation of the different cell types to achieve normal parturition at term.…”
Section: What Is the Role Of Granulocytes In The Choriodecidua Duringmentioning
confidence: 99%
“…Previous studies conducted by our group and others have demonstrated the importance of the choriodecidual microenvironment in spontaneous parturition in humans, strengthening the role of the innate immune system in labor. 17,19,21,22,8083 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 It can also directly modulate the production of the proinflammatory cytokines, IL-6 and IL-8 produced by both the chorion and decidua. 14,15 However, there has been no attempt to date, to integrate the data on the systemic and intrauterine RLN in either normal gestation or in sPTB.…”
Section: Introductionmentioning
confidence: 99%
“…In pregnancy, relaxin is produced by the placenta, membranes and decidua, and exerts both local and systemic effects. Experimental data show that relaxin can augment the intrauterine inflammatory response, affect myometrial contractility through cyclooxygenase‐1 (COX‐1) and COX‐2 activation, and upregulate MMPs. Even so, serum levels of relaxin are not necessarily expected to reflect accurately the local concentration and effects of the hormone at the choriodecidual level.…”
Section: Discussionmentioning
confidence: 99%